From Villages to World Markets: Women and E-Commerce in East Sumba, East Nusa Tenggara - Khaerul Umam Noer (BASKARA : Journal of Business and Entrepreneurship, 2021)
This paper focuses on the use of e-commerce by women weaving craftsmen, in Sumba, East Nusa Tenggara. In 2020, We Are Social noted that 56% of Indonesia's population are active internet users, including 29% of the population are active e-commerce users. The Indonesian Creative Economy Agency report states that 36% of e-commerce traders in Indonesia come from rural areas, especially in Java. Data shows that fashion and craft-based creative industries have a high contribution to the national economy, and for this reason, the government has taken several policies in fostering and developing the creative industry, one of which is by increasing the development of business groups that are under the creative industry, especially those based on fashion and regional crafts. Sumba is known as Pahikung weaving where most of the industrial craftsmen are women. Using the ethnographic method, by interviewing twelve women weaving craftsmen, this paper explains that the marketplace opens up opportunities for better weaving sales by cutting distribution channels so that their products can be directly accepted by consumers, and by promoting through social media, they cut indirect costs. However, there are three main obstacles faced: production costs, distribution, and access to financial services. With this mapping, it is hoped that it will encourage more accommodative policies towards women craftsmen in rural and remote areas in Indonesia.